Dark Triad traits, Facebook intensity, and intrasexual competition. (15th April 2019) - Lyons, Minna; Gillies, Naomi; Brewer, Gayle
Abstract: Intrasexual competition supports the acquisition of new mates and the maintenance of existing relationships. We investigated intrasexual competition in relation to Dark Triad traits (narcissism, Machiavellianism, and psychopathy) and intensity of Facebook use. Men ( n = 61) and women ( n = 164) completed measures assessing intrasexual competition (Buunk & Fisher, 2009), Dark Triad traits (Jones & Paulhus, 2014), and intensity of Facebook use (Ellison, Steinfield, & Lampe, 2007). Machiavellianism and psychopathy were positive predictors for endorsement of intrasexual competition. Narcissism and Facebook intensity did not predict intrasexual competition. Findings are discussed in relation to personality and mate competition. Highlights: We investigated intrasexual competition, Dark Triad traits, and Facebook use. Men and women high on Machiavellianism and psychopathy reported higher competition. Narcissism and Facebook intensity did not predict intrasexual competition.